RANCANG BANGUN DAN UJI KINERJA ALAT PENGERING TEMBAKAU MOLE TIPE EFEK RUMAH KACA (ERK) KONSTRUKSI BAMBU - Wahyu Kristian Sugandi; Ahmad Thoriq; Asep Yusuf; Arif Purwonugroho (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
ABSTRACT Tobacco plants are one of the leading commodities of plantations in Sumedang Regency. The processing process in tobacco which influences the quality of tobacco is the drying and condensation process. Currently the drying process of tobacco mole produced in Sukasari District still uses solar energy which is strongly influenced by weather conditions and is very vulnerable to being contaminated by other materials during drying. The drying process using solar energy requires 7-14 days depending on the weather. To speed up the drying process, it is necessary to design a bamboo construction ERK type mole dryer. The purpose of this research is to design and test the performance of ERK type tobacco mole dryer construction, so that it can speed up the drying process of tobacco in large quantities. The research method uses engineering methods through several stages of the activity process, namely: designing ERK type dryers, functional mixtures, structural designs, technical analysis and performance tests. ERK type mole tobacco dryer bamboo construction that has been made has an overall length of 5 m, a width of 3 m and a height of 2.5 m. Construction of dryers using betung and tie bamboo, walls as coatings for dryers using 6% UV plastic. Based on the analysis using Ansys software, it was found that the shear stress was still below the recommended threshold of 20.42 Pa, while the threshold of petung bamboo was 177 MPa. In the no-load test using an exaust fan, the temperature obtained after 24 hours of data collection in the ERK dryer is equal to 14áµ’C - 46áµ’C and while the temperature outside the ERK dryer is 16.4 - 30.5áµ’C. Decrease in the water content of tobacco produced by this dryer is 66% for 5 days, while outside the dryer is 71% for 14 days. Thermal and drying efficience this dryer is 17,24% and 55,79%. Key word: Design, Performance Test, ERK Dryer, Tobacco Mole, Bamboo